If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(7 + -2m) + 5 = 90 (7 * 5 + -2m * 5) + 5 = 90 (35 + -10m) + 5 = 90 Reorder the terms: 35 + 5 + -10m = 90 Combine like terms: 35 + 5 = 40 40 + -10m = 90 Solving 40 + -10m = 90 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-40' to each side of the equation. 40 + -40 + -10m = 90 + -40 Combine like terms: 40 + -40 = 0 0 + -10m = 90 + -40 -10m = 90 + -40 Combine like terms: 90 + -40 = 50 -10m = 50 Divide each side by '-10'. m = -5 Simplifying m = -5
| 2x^2-8x+15=11 | | 45-x=7 | | -7(2b+1)+(15b-3)=0 | | (-5u^3v^4+9u)+(-5u^3v^4-8u+8u^2v^2)+(-8u^4v^2+8u^3v^4)= | | 1.4q-1.3-1.8q=-1.4q-2.8 | | 4x+23=12x-73 | | 3x+4=59 | | 12-3=10x+3 | | y+34=18 | | 7+2x^2+4x^2=37 | | 5(5x+13)=25 | | 9m+3(m+12)-2= | | 0.45x+.05(2-x)=.10(-55) | | 4x(1-3x)=0 | | 5x+2=-5x+12 | | y=x^2-4x-1 | | 7z-8z=8z-6+4z | | 6w+13=3w-26 | | 3(2x+3)-5= | | -7(1)(-7)= | | 8x=18+5x | | 8x-2=40x+6 | | 3(5x+7)=-48+9 | | 48-x=7-4x | | 2a+6+9a+8= | | 10x-(3x-11)=25 | | x+4=59 | | 9x(x-5)=20x^2-46X | | 4+x=120 | | (2x-5)=5 | | 20-5n= | | 6(x-3)+3=2x+5 |